KEMAMPUAN MENULIS PARAGRAF PERSUASI DENGAN MENGGUNAKAN MEDIA GAMBAR SISWA KELAS X SMA NEGERI 1 PANTAI CERMIN KABUPATEN SOLOK - Eriza, Desi; Chan, Wirsal; Yusandra, Titiek Fujita (Pendidikan Bahasa Indonesia, 2013)
This research is motivated by problems in four of them: (1) when explaining the material students are not much to ask, but when given the task of students impressed task as a burden, (2) students as sume that writing is a difficult learning activities. Recognized the difficulty of writing students to developen idea or ideas in written form, (3) lack of mastery of spelling, punctuation and vocabulary of the students so that the choice of word used lessattractive, (4) absence of the use of instructional media in writing paragraphs. This study uses aquantitative approach with descriptive methods.This study image to describethe ability to writepersuasiveparagraphsusingmediaimagestenth grade studentsof SMA Negeri1MirrorBeachSolok.Furthermore, the abilityto writepersuasiveparagraphsclass XSMANegeri 1MirrorBeachSolokbasedcharacteristicspersuasionparagraph(1) the factquitewellwiththe average value of76.67is inthe range76-85%, (2) the languagecontain a callso as toinvitethe readerquitelesswithan averagevalue of42.67is inthe range36-45%, (3) logicalsentencesconsideredmore than adequate withan averagevalue of75.33is inthe range66-75% and(4) compliancewith thecontents ofthemediaarevery wellqualifiedwithan averagevalue of86.67is inthe range86-95%.Based on thedocument analysisandresults, it canbe concludedthat theabilityto writepersuasiveparagraphsusingmediaimagestenth grade studentsof SMA Negeri1MirrorBeachSolokconsideredmore thanenough. Thisis evidencedbythe averagestudents 70orare in the66-75% range.